CHOICE OF SURGICAL TACTICS IN MULTIPLE CHOLEDOCHOLITHIASIS (World Bulletin of Public Health, 2025)
For a long time, the number of patients with multiple choledocholithiasis caused by various reasons remains high. At the same time, if a child does not have a clinical picture of choledocholithiasis, the diagnosis sounds like gallstone disease, chronic cholecystitis, so patients most often undergo laparoscopic operations, during which revision of the common bile duct for choledocholithiasis is not performed. The choice of surgical tactics for multiple choledocholithiasis necessitates improving diagnostics, optimizing treatment and minimizing operations in patients with this disease.